2011
DOI: 10.1111/j.1757-1707.2011.01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Forest bioenergy climate impact can be improved by allocating forest residue removal

Abstract: Bioenergy from forest residues can be used to avoid fossil carbon emissions, but removing biomass from forests reduces carbon stock sizes and carbon input to litter and soil. The magnitude and longevity of these carbon stock changes determine how effective measures to utilize bioenergy from forest residues are to reduce greenhouse gas (GHG) emissions from the energy sector and to mitigate climate change. In this study, we estimate the variability of GHG emissions and consequent climate impacts resulting from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(112 citation statements)
references
References 47 publications
4
107
0
Order By: Relevance
“…This means that during the remaining years of the forest rotation, the southern forest would emit more CO 2 due to decomposition if the logging residues were not harvested. As a result, the climate mitigation effects per unit of DH produced during one forest rotation from one forest stand would be larger when logging residues are harvested in the south of Sweden, which agrees with the conclusions found in Repo et al [10]. The life cycle impact assessment showed that the average yearly temperature change during the 50 years following the harvest of logging residues was 0.024, 0.030 and 0.032 10 -15 K MJ -1 heat for the southern, central and northern forest stands, respectively, when logging residues were harvested for bioenergy, not including the substitution effect of replacing fossil fuel.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This means that during the remaining years of the forest rotation, the southern forest would emit more CO 2 due to decomposition if the logging residues were not harvested. As a result, the climate mitigation effects per unit of DH produced during one forest rotation from one forest stand would be larger when logging residues are harvested in the south of Sweden, which agrees with the conclusions found in Repo et al [10]. The life cycle impact assessment showed that the average yearly temperature change during the 50 years following the harvest of logging residues was 0.024, 0.030 and 0.032 10 -15 K MJ -1 heat for the southern, central and northern forest stands, respectively, when logging residues were harvested for bioenergy, not including the substitution effect of replacing fossil fuel.…”
Section: Discussionsupporting
confidence: 82%
“…The GWP 100 of the three forest systems was approximately 3.7-3.8 g CO 2 -eq per MJ fuel, only including non-biogenic GHG emissions from forwarding, chipping, transportation, ash recycling and combustion. Previous studies have shown GWP in the range of 1.8-11 g CO 2 -eq MJ -1 fuel [20,19,55,10]. However, comparing results from different LCA studies are often problematic due to differences in system boundaries, functional unit and choice of allocation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Y pul p = r 11 D r 12 1 + r 11 D r 12Ŷ prod + ε 12 (12) where r 11 = a 12 /a 11 , and r 12 = b 12 − b 11 . In the same way, a system of allocative biomass equations was specified to allocate the estimated total residue biomass in Step 1 to the three subcomponents: res + ε 23 (13) where Y stump , Y branch and Y waste represent for stump, branch, and waste biomass in either fresh or dry weight in kg,Ŷ res represents the corresponding predicted total residue biomass in kg from any of the systems of additive equations, r 21 , r 22 , r 23 and r 24 are coefficients, ε 21 , ε 22 and ε 23 are the error terms.…”
Section: Allocative Biomass Equationsmentioning
confidence: 99%
“…Over much of the latter half of the 20th Century, forest harvest residues represented a source of fuelwood for rural communities in many developing countries [1,2], while they were often windrowed, burned and mostly reduced to ashes to return to the soil as part of site preparation for the establishment of the next rotation in developed countries (e.g., [3][4][5]). With the increasing recognition of the role of bioenergy in climate change mitigation since the turn of the 21st Century (see [6][7][8]), forest harvest and timber processing residues have received a renewed focus as a major potential source of woody biomass that can be used to supplement or replace fossil fuels in order to reduce greenhouse gas emissions of energy production [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%